PENGARUH PENGENDALIAN INTERNAL, KOMITMEN ORGANISASI DAN SISTEM INFORMASI AKUNTANSI TERHADAP PENCEGAHAN FRAUD PADA RSIA ZAINAB PEKANBARU - Andini Pratami; Rama Gita Suci (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This research aims to determine and analyze the influence of internal control, organizational commitment, and accounting information systems on fraud prevention. This research is quantitative research. The population in the study was 222 employees. The sample in this study used simple random sampling with a sample size of 69 employees. The data source in this research uses primary data which comes from the results of data collection using a questionnaire. Data analysis in this research uses multiple linear regression analysis with the help of the SPSS 25 program. The results of this research show that internal control, organizational commitment and accounting information systems influence fraud prevention.